2007
DOI: 10.1111/j.1365-2273.2007.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism: do perioperative biochemical variables correlate with parathyroid adenoma weight or volume?

Abstract: Biochemical parameters will not accurately predict the size of a parathyroid adenoma. The size of a parathyroid adenoma does not correlate with postoperative calcium levels and is therefore not useful as a predictor of postoperative hypocalcaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
42
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 13 publications
6
42
2
1
Order By: Relevance
“…reported a series of 63 patients in whom there was a significant correlation between calcium and PTH levels and PTA weight and volume. More recent studies, which evaluated cohorts of about 70 patients, found no correlation at all …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…reported a series of 63 patients in whom there was a significant correlation between calcium and PTH levels and PTA weight and volume. More recent studies, which evaluated cohorts of about 70 patients, found no correlation at all …”
Section: Discussionmentioning
confidence: 93%
“…The value of preoperative calcium and PTH levels as a predictor of intraoperative PTA dimensions remains undetermined. Some studies reported a statistically significant correlation between preoperative calcium and PTH levels and PTA weight whereas others failed to support these findings . Furthermore, only two studies addressed the potential association between blood calcium and PTH levels and histological features of PTAs, with inconsistent results: one implied that predominantly, chief‐cell PTAs are associated with more severe clinical manifestations than clear‐cell adenomas but the other found no difference …”
mentioning
confidence: 99%
“…In multivariate analysis, patients with PC did not show a statistically significant difference in serum levels of iPTH compared to those with benign PHPT. The relationship between preoperative serum PTH levels and the size of a parathyroid adenoma or carcinoma is controversial (25, 26). In the present study, serum iPTH levels were correlated with tumor size in patients with parathyroid adenoma but not in patients with PC.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from different studies have been variable. Randhawa et al [12] observed no relationship between serum calcium and PTH levels and adenoma weight or volume while other studies [7,13,14] demonstrated significant correlations between preoperative serum calcium and PTH and adenoma weight. No consensus has been reached, however, on whether parathyroid weight alone can predict postoperative hypocalcaemia.…”
Section: Discussionmentioning
confidence: 89%
“…Correlation between serum PTH and adenoma weight has been studied by several authors [7][8][9][10][11][12][13][14], as well as serum calcium and adenoma weight [7]. However, results from different studies have been variable.…”
Section: Discussionmentioning
confidence: 99%